Study Effect of Chitosan-Epichlorohydrin Macropore Beads on Decreasing the Value of Total Dissolved Solid (TDS) and Dyes in Sasirangan Liquid Waste Treatment - Ariyani, Dahlena; Hilma, Nabila Khairiyatul; Utami, Umi Baroroh Lili; Santoso, Uripto Trisno; Mujiyanti, Dwi Rasy (Indonesian Journal of Chemical Research, 2023)
Sasirangan liquid waste contains contaminants that are quite dangerous, characterized by high values of total dissolved solids and dyestuffs. This study aims to determine the effect of dose and pH on chitosan-epichlorohydrin macropore beads. The parameters of the measured waste are total dissolved solids and dyestuffs. The process of absorption of sasirangan liquid waste characterizes by FTIR. The results showed that chitosan-epichlorohydrin beads that interacted with sasirangan liquid waste had optimum results at a chitosan dose of 600 mL/L, with a decrease in the total value of dissolved solid by 2161 mg/L and a decrease in dye by 84.78%. Chitosan-epichlorohydrin beads at pH against total dissolved solid gave optimum results at pH 7 with a reduction in the total dissolved solid value of 2269 mg/L, while pH against dyestuffs gave optimum results at pH 3 with a decrease of 94.09%. The interaction between chitosan and chitosan-epichlorohydrin beads occurred a shift in wave numbers from 943 cm-1 to 932 cm-1 showing the C-O-C group and the chitosan-epichlorohydrin beads spectra with waste at wave numbers 3013-3618 cm-1 to 3007-3631 cm-1 the O-H vibration group overlapped the N-H vibration and showed the result that the beads Chitosan-epichlorohydrin/adsorb sasirangan liquid waste.